Navigating relationships and tensions: how professionals who treat substance use disorders view their role in preventing child abuse and neglect - Paulo Padilla-Petry; Nuria Fuentes-Peláez; Anna Fantova-Romero (Child Protection and Practice)
Background: The potential negative effects of caregivers’ substance use disorders (SUDs) on their parenting are well documented, but the intervention of healthcare professionals treating these disorders in cases of child abuse and neglect (CAN) is constrained by ethical dilemmas and mistrust of child welfare services (CWS). Many studies have explored the synergies between SUD treatments and developing parenting skills, but few studies have explored these professionals' diverse perceptions and experiences – ranging from doubts and challenges to constructive ideas and practices that address parenting and treatment needs. Objective: This study aimed to explore healthcare professionals' perceptions and experiences regarding the tensions, obstacles, opportunities and good practices related to detecting potential CAN and promoting changes in their patients’ parenting. Participants and setting: Twenty healthcare professionals from various services within the Catalan Drug Abuse Care Centre Network (Spain) participated in the study. Methods: Two focus groups discussed the issues and good practices surrounding the detection and intervention in possible cases of CAN. The transcriptions underwent reflexive thematic analysis building 7 themes. Findings: The participants cited reasons for not intervening in their patients' parenting. They discussed the importance and fragility of the therapeutic bond, structural deficiencies in their services, and the challenges of working with CWS. They also described conditions and practices that help improve caregivers’ parenting such as restoring damaged bonds. Conclusion: The full range of healthcare professionals' experiences and perceptions regarding their patients’ parenting and child welfare must be contemplated in programs aimed at integrating family support with the treatment of SUDs.